Phenolic compounds isolated from Pilea microphylla prevent radiation-induced cellular DNA damage - Punit Bansal; Piya Paul; Pawan G. Nayak; Steve T. Pannakal; Jian-hua Zou; Hartmut Laatsch; K.I. Priyadarsini; M.K. Unnikrishnan (Elsevier, 2011)
Six phenolic compounds namely, quercetin-3-O-rutinoside (1), 3-O-caffeoylquinic acid (2), luteolin-7-O-glucoside (3), apigenin-7-O-rutinoside (4), apigenin-7-O-β-d-glucopyranoside (5) and quercetin (6) were isolated from the whole plant of Pilea microphylla using conventional open-silica gel column chromatography and preparative HPLC. Further, these compounds were characterized by 1D, 2D NMR techniques and high-resolution LC-MS. Compounds 1-3 and 6 exhibited significant antioxidant potential in scavenging free radicals such as DPPH, ABTS and SOD with IC50 of 3.3-20.4 μmol/L. The same compounds also prevented lipid peroxidation with IC50 of 10.4-32.2 μmol/L. The compounds also significantly prevented the Fenton reagent-induced calf thymus DNA damage. Pre-treatment with compounds 1-3 and 6 in V79 cells attenuated radiation-induced formation of reactive oxygen species, lipid peroxidation, cytotoxicity and DNA damage, correlating the antioxidant activity of polyphenols with their radioprotective effects. Compounds 1, 3 and 6 significantly inhibited lipid peroxidation, presumably due to 3',4'-catechol ortho-dihydroxy moiety in the B-ring, which has a strong affinity for phospholipid membranes. Oxidation of flavonoids, with catechol structure on B-ring, yields a fairly stable ortho-semiquinone radical by facilitating electron delocalization, which is involved in antioxidant mechanism. Hence, the flavonoid structure, number and location of hydroxyl groups together determine the antioxidant and radioprotection mechanism.